Using the Ensuring Quality Information for Patients Tool to Assess Patient Information on Appendicitis Websites: Systematic Search and Evaluation - Ghani, Shahi; Fan, Ka Siu; Fan, Ka Hay; Lenti, Lorenzo; Raptis, Dimitri (JMIR Publications, 2021)
BackgroundAppendicitis is a common surgical problem among the young adult population, who are likely to use the internet to obtain medical information. This information may determine the health-seeking behavior of an individual and may delay medical attention. Little is known regarding the quality of patient information on appendicitis on the internet, as this has not been previously studied. ObjectiveThe aim of our study was to identify the quality of information regarding appendicitis on websites intended for the public. MethodsWe conducted a systematic review of information on appendicitis available online using the following 4 search terms in google: "appendicitis," "appendix," "appendectomy," and "appendicectomy". The top 100 websites of each search term were assessed using the validated Ensuring Quality Information for Patients (EQIP) tool (score 0-36). ResultsA total of 119 websites met the eligibility criteria for evaluation. The overall median EQIP score for all websites was 20 (IQR 18-22). More than half the websites originated from the USA (65/119, 54.6%), and 45.4% (54/119) of all websites originated from hospitals, although 43% (23/54) of these did not mention qualitative risks from surgery. Incidence rates were only provided for complications and mortality in 12.6% (15/119) and 3.3% (4/119) of all websites, respectively. ConclusionsThe assessment of the quality and readability of websites concerning appendicitis by the EQIP tool indicates that most sites online were of poor credibility, with minimal information regarding complication rates and mortality. To improve education and awareness of appendicitis, there is an immediate need for more informative and patient-centered websites that are more compatible with international quality standards.